PRODUKSI MINYAK BIJI KAPUK DALAM USAHA PEMAN FAATAN BIJI KAPUK SEBAGAI SUMBER MINYAK NABATI - Yuniwati, Murni (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Kapok tree (Ceiba pentandra) is a member of small class Malvales, family Malvaceae. The plant is native to the shout America, Central of America and Caribia. It grow well at the tropical region. In fact the kapok seed contains fatty acid with higher economic value which is called kapok oil. Oil of kapok seed can be obtained from solid-liquid extraction methode. In this investigation, the extraction of kapok seed was carried out in the stirred tank with ethanol as a solvent. Extract was distilled to separate kapok seed oil from solvent. The variable of investigation were extraction temperature , stirring speed, ratio between solvent volume and mass of kapok seed , and size of kapok seed. Tthe extracted oil was analyzed by using gas chromatography to determine the fatty acid composition. The optimum condition of kapok seed extraction were obtained at boiling point of ethanol Â± 78 oC, stirring speed 400 rpm, ratio between solvent volum and mass of kapok seed is 16mL: 1gr, and size of kapok seed (-30 / 40 ) mesh or average diameter 0,065 cm. The corelation between mass transfer coefficient and these variables is shown in the dimensionless equation below : Sh = 0,132 Re(0,5004). Sc 0,651. with the average error 0,95 %